Targeting dysregulated intracellular immunometabolism within synovial microenvironment in rheumatoid arthritis with natural products - Hu, Shengtao; Lin, Ye; Tang, Yuanyuan; Zhang, Junlan; He, Yini; Li, Gejing; Li, Liqing; Cai, Xiong (Frontiers in Pharmacology, 2024)
Immunometabolism has been an emerging hotspot in the fields of tumors, obesity, and atherosclerosis in recent decades, yet few studies have investigated its connection with rheumatoid arthritis (RA). In principle, intracellular metabolic pathways upstream regulated by nutrients and growth factors control the effector functions of immune cells. Dynamic communication and hypermetabolic lesions of immune cells within the inflammatory synovial microenvironment contributes to the development and progression of RA. Hence, targeting metabolic pathways within immune subpopulations and pathological cells may represent novel therapeutic strategies for RA. Natural products constitute a great potential treasury for the research and development of novel drugs targeting RA. Here, we aimed to delineate an atlas of glycolysis, lipid metabolism, amino acid biosynthesis, and nucleotide metabolism in the synovial microenvironment of RA that affect the pathological processes of synovial cells. Meanwhile, therapeutic potentials and pharmacological mechanisms of natural products that are demonstrated to inhibit related key enzymes in the metabolic pathways or reverse the metabolic microenvironment and communication signals were discussed and highlighted.